Motion estimation using inertial sensor technology with applications to sporting exercises - Gasser, M. (New Studies in Athletics, 2014)
The ability to measure performance related indicators in training and competitive environments is important for coaches in a number of sports. The testing and monitoring of athletes outside of the laboaratory is a comparatively new field that has been facilitated by advancements in micro-electromechanical systems technology. The aim of this study was to test the efficacy of systems using micro accelerometers to measure foot-ground contact time, a key parameter in running performance, and quickly provide feedback. Experiments were conducted to a) compare results of single steps from jogging and running using different types of devices and b) compare results for several sprint strides from four individuals. The results show that accurate measurement of ground contact time is possible outside of a laboratory with inertial sensors and the developed algorithm. With the use of a smartphone or tablet to control the sensors and visualise the results, the high precision, low cost, minimal size and ease of the tested system makes it perfect for use by elite coaches and recreational athletes.